Crowdsourcing: como a sabedoria das multidões pode interessar ao campo de pesquisa e ação da Ciência da Informação - Lu, Yi Chieh (Universidade Federal de São Carlos, 2019)
With the advent of the Internet and the constant adaptation of the Web, the space of exchange of information with different interests and needs has been reshaping the way of research of individuals connected to the network, especially the way of producing information and knowledge in this space. Due to it, more and more discussions about Crowdsourcing are emerging as a way of producing new knowledge. It is a model of information production that provides for collective collaboration and takes advantage of the “wisdom of the crowd” to generate innovation. In this sense, the objective of this research is to investigate the extent to which Crowdsourcing is used as a resource for the production of knowledge and innovation for the field of research and action of Information Science, within the University Libraries, aiming to identify possibilities for approaching librarians with their internal and external community. As specific objectives, it is necessary to verify how much this model has been explored in the scope of the Integrated Library System of UFSCar, since it is understood that these Libraries are configured as indispensable equipment to optimize the production of knowledge and innovation. Methodologically, the work was based on the Systematic Review of Literature, developing bibliographic surveys in national databases - BRAPCI and BENANCIB, and international - LISTA and SOCUPUS (multidisciplinary) databases. The profile of the Brazilian researcher on crowdsourcing was also analyzed through the Lattes Platform, using Lattes Machines and VantagePoint tools. Direct observation was carried out on WebSites of University Libraries for identification and mapping of crowdsourcing practices. Finally, a Case Study of the UFSCar Community Library was conducted to identify potential applications of crowdsourcing, describing the proposed implementation of Starteca. The results reveal that there is a lack of knowledge about crowdsourcing in the field of research and practice in Information Science, especially in the scope of Brazilian university libraries, which is a common practice abroad in public libraries in general. It also revealed the change of position of the librarians in face of the community’s needs, who are no longer imprisoned only access and material physical support, promoting in these places an environment of collaboration and collective construction of solutions, and can be used also for crowdsourcing application in physical environment - Starteca, space to undertake - by the library. Therefore, it is concluded that crowdsourcing is an innovative resource for Information Science within the University Libraries, since it is possible to innovate its practices through the wisdom of the crowd, opening the doors and opportunities for the connected society to contribute, approaching the community and giving visibility to the library. At the same time, it is possible to be a tool to overcome the financial crises encountered today, becoming a creative and active way for the library to collaborate with its community. In this way, it is possible to boost products and services, since these are inputs to support the development of new knowledge and generation of innovation. However, prior to this, the library must adopt mechanisms to approach its users, welcoming them to be part of the space, becoming an equipment that fosters sharing, exchanges and problem solving together, their value to the community through active attitude.
Crowdsourcing: how crowd wisdom can interest the Information Science research and action field
Keywords: Crowdsourcing; Ciência da Informação; Biblioteca Universitária; Inteligência Coletiva; Sabedoria da Multidão; Information Science; Library University; Collective Intelligence; Wisdom of the Crowd; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO